L’abandon de la carrière criminelle : quelques témoignages - Pinsonneault, Pierre (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1985)
This article summarizes some of the findings of research done on the relinquishing of a criminal career. It is based on about twenty interviews, carried out between July and November 1984, with multirecedivist ex-criminals who had abandoned their criminal careers for at least five years prior to the study. We isolated the factors that dissuaded them from continuing this way of life as well as others that caused them to adopt a more conventional lifestyle. It is a question of the difficulties connected with a criminal way of life — whether it be with one's criminal colleagues, rival gangs, informers, or the police, lawyers and the courts. There follows a series of bad experiences concerning prison life : the accumulation of sentences and years of prison, the living conditions, problems with the officers and guards, the presence of other inmates. But there are also positive things one discovers in prison whether it be new knowledge, new responsibilities or the help of people outside, such as Alcoholics Anonymous or the chaplains or at the emotional level, of a wife or mate. We see, based on these factors, some of the difficulties that the ex-criminal must face if he wants to persevere in following a conventional lifestyle.